Management of differentiated thyroid carcinoma. - Fakir, AY; Bhuyan, AH; Rahman, MM; Khan, FM (Mymensingh Medical Journal, 2012)
Mymensingh Med J. 2011 Oct;20(4):625-31 The abstract of this article is available on the PubMed website